2018
DOI: 10.1029/2018jc014176
|View full text |Cite
|
Sign up to set email alerts
|

Volume and Transport of Eddy‐Trapped Mode Water South of the Kuroshio Extension

Abstract: Mesoscale eddies play an important role in transporting North Pacific subtropical mode water (STMW). Using eddy samples adopted from a 3‐day and 0.1° ocean model output spanning from 1980 to 2014, this study quantifies the eddy‐trapped STMW volume and transport south of the Kuroshio Extension. Based on the shape of their isopycnals, anticyclonic eddies (AEs) in the region are classified into two types. The first type (AE1) has a lens‐like structure of isopycnals, and the second type (AE2) has downward bending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…In the North Pacific, the subtropical mode water formed in the deep mixed layer in late winter because of intense convection is known as STMW [40]. STMW is significantly modulated by mesoscale eddies and thick (thin) STMW is co-located with anticyclonic (cyclonic) eddies [31,41,42]. The potential vorticity is used to identify STMW, which is defined as [43]: The criterion of T z ≥ 0.02°C/m is adopted to identify the permanent thermocline.…”
Section: Stmwmentioning
confidence: 99%
“…In the North Pacific, the subtropical mode water formed in the deep mixed layer in late winter because of intense convection is known as STMW [40]. STMW is significantly modulated by mesoscale eddies and thick (thin) STMW is co-located with anticyclonic (cyclonic) eddies [31,41,42]. The potential vorticity is used to identify STMW, which is defined as [43]: The criterion of T z ≥ 0.02°C/m is adopted to identify the permanent thermocline.…”
Section: Stmwmentioning
confidence: 99%
“…An understanding of the formation and circulation of water masses will help to improve our knowledge of long‐term thermohaline changes and variations in the upper ocean. Recently, the role of eddies in water mass formation (e.g., Kouketsu et al, ) and spreading (e.g., Shi et al, ; Zhang et al, ) has been recognized. To develop our understanding of long‐term changes in the upper ocean, further examination of the formation, circulation, and dissipation of water masses using both observational data and eddy‐resolving models will be useful.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The θ anomaly derived from MLT in the outcrop region is detected widely on the isopycnal surface at lags of 2 and 3 years (Figures c and d), suggesting a rapid southward spread of the θ anomalies. Since eddy activity is elevated in the western to central part of the subtropical gyre compared to the eastern part (e.g., Qiu & Chen, ), mesoscale eddies (Shi et al, ; Zhang et al, ) and/or submesoscale phenomena may play important roles in the rapid distribution of the θ anomalies. The high‐correlation regions shrink to the east of 150°E at lags of 4 and 5 years and do not reach regions farther west (Figures e and f).…”
Section: Mechanism Of Long‐term Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other is the southward translation of the anticyclone itself, which accompanies large volume of low PV water. Shi et al () compared the differences between different mesoscale oceanic eddies based on the shape of their isopycnals in transporting the STMW. Liu and Peiliang () found that in the nongeneration months (from May to Dec), the “trapped depth” of the anticyclone is deeper than that of the cyclone, namely, the anticyclone can trap thicker STMW to its center and then transports it southward.…”
Section: Introductionmentioning
confidence: 99%